Assessment of occupational safety and health awareness of public servants in the workplace / Rosley Jaafar ... [et al.] - Jaafar, Rosley; Umar, Norazah; Ibrahim, Anas; Abdul Halim, Muhammad Aiman (Universiti Teknologi MARA, Kedah, 2024)
Occupational safety and health (OSH) awareness is a constant acknowledgment that every employee must have, and it goes beyond what they have learned in the safety and health training workshop. This study was conducted to identify and evaluates based on the seven aspects (occupational safety and health policy, commitment and attitude, standard operating procedure, training, safety and health committee, equipment, and environment) of OSH awareness of Universiti Teknologi MARA Cawangan Pulau Pinang (UiTMCPP) staff in the workplace. There were 193 respondents from various faculties and departments. Questionnaires were used as the instrument to collect the data and the Statistical Package for the Social Sciences (SPSS) version 20 was used to analyse it. The frequency, percentage, and mean score were used to identify the level of respondents' awareness. This study found that the level of OSH awareness among UiTMCPP staff in the workplace is at a high level with an overall mean score of 4.44. OSH policy with an average mean score of 4.90 is a dominant factor that contributed to OSH awareness level compared to other factors. It is hoped that this study can be a source of reference for the UiTM management and other organisation in increasing the level of OSH awareness of their employees.